PAWELAWEL JARKOWSKI’S ATTEMPTS TO CLASSIFY BIBLIOGRAPHY PHENOMENA (IN THE CONTEXT OF THE EUROPEAN BOOK SCIENCE BIBLIOGRAPHY PARADIGM OF THE LATE 18th –EARLY 19th CENTUR - ČEPYTĖ, JULIJA (Knygotyra, 2010)
Pawel Jarkowski (1781–1845) is a pioneer of teaching bibliography in the former territory of Lithuanian and Polish State Kremenets lyceum (in the Ukraine) which belonged to Vilnius university (he lectured there in 1809–1832). His legacy comprises manuscripts and published lecture plans, very generally researched by Polish, Russian, Ukrainian and Lithuanian scientists paying attention to various attitudes towards bibliography, the influence of the pioneers and coevals in bibliography science research and other aspects. The aim of this article is to reveal P. Jarkowski’s attempts to classify bibliography phenomena, and especially bibliography in real (or narrow) sense, and bibliographical resources including classification ideas, principles, influences, and interrelationships in the content of the European book science bibliography paradigm of the late 18th century – early 19th century. The research is based on historical, logical and comparative methods as well as on the analysis of sources and literature. The main sources under analysis are two published drafts of his bibliology lectures (1814–15 a shorter and in 1818 a more explicit variant). The object of our research is the structural schemes of these drafts. They are analysed dealing with their contents, form, function and formal logical aspects, analysing respectively subject, functional and formal logical structure of bibliography. The attempts of classifying bibliography phenomena related to the latter structure are analysed on some levels, such as 1) entirety (bibliography in Abstractthe extensive sense of bibliology), 2) bibliography in its real (narrow) sense, 3) bibliography resources. Bibliography (bibliology) schemes as a whole reveal not the kinds of bibliography but their subject structure. However, these schemes can be characterized as having the following features of classifications: the multilevel hierarchical structure of subject contents, a complex form of the scheme with a strict numeration, the dichotomy principle of classification, the influence of science and bibliography classifications. The same can be said about the bibliography in the real sense as a whole. But we can also detect fragments (microclassifications) of different phenomena, especially those of bibliographical resources: 1) catalogues, 2) subsidiary books used for keeping the order in the library (works that are obtained, discarded, loaned). All of them are connected with a certain stock (the kind of librarian or institutional bibliography production). P. Jarkowski presents a very original for his time classification of bibliographical resources which are not connected with any stock in his scheme of classification of sciences. His classification of bibliographical resources is based on the principles of hierarchy and dichotomy, the latter having become the ground of classification. This makes him different from his predecessors and contemporaries, but these classifications did not reflect the variety of bibliography tools and the advanced terminology of his time. P. Jarkowski did not intend to specially classify bibliography and its different phenomena. While elaborating the book science bibliography paradigm, he did not try to create new kinds of knowledge. He only made use of the material created by his predecessors (especially M. Denis) and contemporaries, which was valuable for preparing librarianship specialists. The frequent changing of the title and content of his course shows his quest for and reaction to innovations in this field. Original solutions were reached by creatively using bibliology achievements of other specialists. For instance, intercepting the kinds of catalogues from his predecessors, he classified them in his own original way, accepting some of them while rejecting others. He was the pioneer in the bibliography science, who classified subsidiary books as bibliographical resources for keeping the order in a library. P. Jarkowski is better known for his achievements in spreading bibliography and book science knowledge for would-be specialists in librarianship. His activity in this field was the sphere of interest among his contemporaries and subsequent professionals. P. Jarkowski is part of Lithuanian, Polish, as well as Russian and Ukrainian bibliography and book science history.
Keywords: ...